PENGARUH PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) AKAR BAMBU DAN PUPUK KNO3 TERHADAP PERTUMBUHAN DAN HASIL KEDELAI EDAMAME PADA TANAH GAMBUT - Syahbani, La Muhammad Imam; Maulidi, Maulidi; Zulfita, Dwi (Fakultas Pertanian, Universitas Janabadra, 2024)
The improvement of edamame soybean on peat soil is done by applying PGPR bamboo root and KNO3 fertilization. The purpose of the study was to determine the effect of the interaction between bamboo root PGPR concentration and KNO3 dosage and to determine the best concentration of bamboo root PGPR and KNO3 dosage on the yield and growth of edamame soybean plants on peat soil. This study uses a Factorial Complete Randomized Design (CRD) consisting of 2 treatment factors repeated 3 times. The first factor is PGPR bamboo root (P) consisting of 3 levels (p1 = 15 ml/L, p2 = 20 ml/L, p3 = 25 ml/L) and KNO3 fertilizer (K) consisting of 3 levels (k1 = 500 kg/ha equivalent to 2.5 g/plant, k2 = 600 kg/ha equivalent to 3 g/plant, k3 = 700 kg/ha equivalent to 3.5 g/plant). Based on the results showed that there was an interaction between the application of PGPR and KNO3 fertilizer on the growth and yield of edamame soybean on peatland and the interaction between PGPR concentration of 20 ml/L and KNO3 fertilizer dose of 500 kg/ha equivalent to 2.5 g/plant is an effective dose to increase the growth and yield of edamame soybean on peat soil.